2012
DOI: 10.1186/1749-7922-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Complicated intra-abdominal infections in Europe: preliminary data from the first three months of the CIAO Study

Abstract: The CIAO Study is a multicenter observational study currently underway in 66 European medical institutions over the course of a six-month study period (January-June 2012).This preliminary report overviews the findings of the first half of the study, which includes all data from the first three months of the six-month study period.Patients with either community-acquired or healthcare-associated complicated intra-abdominal infections (IAIs) were included in the study.912 patients with a mean age of 54.4 years (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Several non-albicans Candida species have been isolated during IAIs, but most have never been experimentally tested as causative agents (8,33). Using the polymicrobial IAI model, five NAC species that vary in ability to undergo morphogenesis were tested for virulence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several non-albicans Candida species have been isolated during IAIs, but most have never been experimentally tested as causative agents (8,33). Using the polymicrobial IAI model, five NAC species that vary in ability to undergo morphogenesis were tested for virulence.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, we have demonstrated that C. albicans morphogenesis is not required to induce synergistic lethality during IAIs with S. aureus (23). Recognizing that NAC species vary in morphology and ability to undergo morphogenesis (29,30), reside within the gastrointestinal tract (31,32), and have been shown to cause IAIs (8,33), it is important to extend the pathogenesis studies to NAC species and further investigate the role of pathways that regulate morphogenesis and virulence during IAIs.…”
mentioning
confidence: 99%
“…Gram-negative bacteria are responsible for the majority of healthcare-associated infections, including urinary tract infections [1], intra-abdominal infections [2] and pneumonia [3], and are an important cause of nosocomial bloodstream infections (BSIs) [4]. Infections caused by Gram-negative bacteria have features that are of particular concern; in particular, Gram-negative bacteria are highly adaptive and often possess multiple mechanisms of antibiotic resistance, especially in the presence of antibiotic selection pressure [5].…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, an increased prevalence of infections caused by antibiotic-resistant pathogens, including methicillin-resistant Staphylococcus aureus , vancomycin-resistant Enterococcus species, carbapenem-resistant Pseudomonas aeruginosa , extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella species, multidrug-resistant Acinetobacter species, and Candida species has been observed, particularly in cases of intra-abdominal infection [242-244]. …”
Section: Introductionmentioning
confidence: 99%